Hydrodynamic and absorption studies of carbon dioxide absorption in aqueous amide solutions using a bubble column contactor - Blanco,A. (2013)
The present work analyses the carbon dioxide absorption process in aqueous n-alkylpyrrolidones solutions, from the point of view of hydrodynamic studies as well as mass transfer, using a bubble column contactor. An analysis of the influence of solute concentration and gas flow-rate is complemented by the study of the effect caused by the alkyl group on the hydrodynamics and mass transfer. The presence of this kind of substance produces a decrease in mass transfer rate, but on the basis of interfacial area and mass transfer coefficient values, ethyl-2-pyrrolidine (EP) shows suitable characteristics to replace methyl-2-pyrrolidine (MP) in gas separation processes due to its lower safety problems.